Exercise ID278

Algebra → Roots → Simplifying
[Level: ] [Number of helps: 0] [Number of pictures: 0] [Number of steps: 14] [Number of characters: 0]

Simplify the following expression:

1+a·1+a33a·39+18a-1+9a-23

1+a·1+a33a·39+18a-1+9a-23 =1+a·1+a333a·39+18a+9a23 =1+a463a·39a2+18a+9a23 =1+a463a·3a29a2+18a+93 =1+a463a·3a49a2+2a+13 =1+a427a36·3a481a2+2a+123 =1+a427a36·3a481a2+2a+126 =1+a427a3·3a4811+a226 =1+a427a3·3a4811+a46 =3a27·816 =a9·816 =a69·816 =a67296 =a63
A=1+a·1+a33a·39+18a-1+9a-23=a63
Start the solution
Restart the solution
Final solution
Hide the final solution
Entire solution!
Hide the entire solution!
Theory
Hide theory